Timing of gun fire influences sprinters' multiple joint reaction times of whole body in block start - Otsuka, M.; Kurihara, T.; Isaka, T. (Frontiers in Psychology, 2017)
Experienced sprinters are specifically adapted to pre-planning an advanced motor program. Herein, sprinters are able to immediately accelerate their center of mass forward with a whole-body coordinated motion, following a steady state crouched position. We examined the effect of variable timing of reaction signals on multiple joint reaction times (RT) and whole-body RT for specialist sprinters. Twenty well-experienced male sprinters performed five start-dashes from a block start under five variable foreperiod (FP) length conditions (1.465, 1.622, 1.780, 1.938, and 2.096 s), with trials randomly timed between a warning and an imperative tone. Participants` sprinting motion and ground reaction forces of their four limbs during the block start were measured simultaneously. Whole-body RT was significantly shorter when FP length was longer; the values of whole-body RT were 117 ± 5 ms, 129 ± 5 ms, 125 ± 4 ms, 133 ± 6 ms, and 156 ± 8 ms in the 2.096, 1.938, 1.780, 1.622, and 1.465-s FP-length conditions, respectively. A repeated-measures analysis of variance found a significant joint-by-FP length interaction in joint-moment RT. These findings suggest that FP length affects coordinated motion in four limbs and whole-body RT. This information will be able to lead to new methods for start signals in sprint running events and advance our understanding of the association between FP length and dynamic coordinated motion.